Hambatan, peluang, dan strategi skrining dua arah tuberkulosis dan diabetes mellitus: A literature review - Reynaldi, Andrean; Juniarti, Neti; Sari, Sheizi Prista (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: The increasing prevalence of tuberculosis (TBC) and diabetes mellitus (DM) comorbidities poses a major challenge for global health systems. DM increases susceptibility to TBC, while TBC worsens glycaemic control in DM patients, which raises the risk of complications and mortality. The WHO notes that many TBC patients also have DM, and vice versa, requiring an integrated care approach. In response, the WHO and The Union developed the Collaborative Framework for the Management of TBC and DM to support bidirectional screening and integrated management, aiming to enhance awareness and improve the quality of TBC-DM patient management. Purpose: To identify the barriers, opportunities, and strategies in implementing bidirectional screening for tuberculosis and diabetes mellitus patients. Method: Literature review research (narrative review) and article search were conducted using the PCC (Population, Concept, Context) framework using literature sources taken from four databases: PubMed, SAGE Journals, Scopus, and Taylor & Francis. Keywords used include: challenges OR barriers OR difficulties AND opportunities OR success OR possibilities AND strategies OR strategies AND two-way AND screening AND TB OR mycobacterium tuberculosis infection OR TB AND comorbidities OR comorbidities AND diabetes mellitus OR DM. Article inclusion criteria include articles published in 2014-2024, full text, open access, academic journals, written in English and Indonesian, and original research. Results: This review identified barriers to implementing two-way screening for TB and DM, such as lack of patient awareness, shortage of health workers, and limited diagnostic tools. However, there are opportunities to improve screening through integration of TB and DM services, private sector involvement, and community-based screening. Strategies to overcome barriers and capitalize on opportunities include better training of health workers, provision of diagnostic tools, and patient education to increase participation in screening. Conclusion: Implementation of bidirectional screening for TB and DM faces several barriers, including lack of patient awareness, social stigma, and limited access and equipment in health facilities, especially in rural areas. In addition, shortage of health workers and limited financing in the health system undermine the implementation of screening. Keywords: Diabetes Mellitus; Bidirectional Screening; Tuberculosis. Pendahuluan: Meningkatnya prevalensi komorbiditas tuberkulosis (TBC) dan diabetes melitus (DM) menjadi tantangan besar bagi sistem kesehatan global. DM meningkatkan kerentanan terhadap TBC, sementara TBC memperburuk pengendalian glikemik pada pasien DM, dan meningkatkan risiko komplikasi serta kematian. WHO mencatat bahwa banyak pasien TBC juga menderita DM dan sebaliknya, sehingga diperlukan pendekatan perawatan yang terintegrasi. Menanggapi hal ini, WHO dan The Union mengembangkan collaborative framework for the management of TBC and DM untuk mendukung skrining dua arah dan manajemen terintegrasi untuk meningkatkan kesadaran dan kualitas manajemen pasien TBC-DM. Tujuan: Untuk mengidentifikasi hambatan, peluang, dan strategi dalam pelaksanaan skrining dua arah untuk pasien tuberkulosis dan diabetes melitus. Metode: Penelitian tinjauan pustaka (narrative review) dan pencarian artikel dilakukan dengan kerangka PCC (Population, Concept, Context) menggunakan sumber literatur yang diambil dari empat basis data: PubMed, SAGE Journals, Scopus, dan Taylor & Francis. Kata kunci yang digunakan meliputi: challenges OR barriers OR difficulties AND opportunities OR success OR possibilities AND strategy OR strategies AND bidirectional AND screening AND tuberculosis OR mycobacterium tuberculosis infection OR TB AND comorbidities OR comorbidity AND diabetes mellitus OR DM. Kriteria inklusi artikel antara lain, artikel yang dipublikasi tahun 2014-2024, full-text, akses terbuka, jurnal akademik, ditulis dalam bahasa Inggris dan Indonesia, serta penelitian asli. Hasil: Tinjauan ini mengidentifikasi hambatan dalam pelaksanaan skrining dua arah untuk TBC dan DM, seperti kurangnya kesadaran pasien, kekurangan tenaga medis, dan keterbatasan alat diagnostik. Namun, terdapat peluang untuk meningkatkan skrining melalui integrasi layanan TBC dan DM, keterlibatan sektor swasta, dan skrining berbasis komunitas. Strategi untuk mengatasi hambatan dan memanfaatkan peluang ini meliputi pelatihan tenaga kesehatan yang lebih baik, penyediaan alat diagnostik, dan edukasi pasien untuk meningkatkan partisipasi dalam skrining. Simpulan: Implementasi skrining dua arah untuk TBC dan DM menghadapi berbagai hambatan, termasuk kurangnya kesadaran pasien, stigma sosial, serta keterbatasan akses, dan peralatan di fasilitas kesehatan, terutama di daerah pedesaan. Selain itu, kekurangan tenaga kesehatan terlatih dan terbatasnya pendanaan dalam sistem kesehatan memperburuk tantangan implementasi skrining. Kata Kunci: Diabetes Mellitus; Skrining Dua Arah; Tuberkulosis.